Pengaruh Akuntansi Pertanggungjawaban pada Efektivitas Pengendalian Biaya dengan Motivasi Kerja sebagai Pemoderasi - Ayusta Devi Savitri, Komang; Sri Harta Mimba, Ni Putu (E-Jurnal Akuntansi; Vol 30 No 8 (2020)DO - 10.24843/EJA.2020.v30.i08.p03, 2020)
A shopping center has extensive operational activities so that managers are unable to control costs without the help of other parties. Required application of responsibility accounting in helping to actualize the delegation of authority and responsibility in order to achieve effective cost control. The purpose of this study is to obtain empirical evidence about the effect of the application of accountability accounting on the effectiveness of cost control with work motivation as a moderating research. This study was conducted by taking the population of shopping centers in Gianyar Regency. Through the saturated sampling method the researcher obtained 37 research samples. The analysis technique used is Moderate Regression Analysis. The results obtained are the responsibility of accounting has a positive effect on the effectiveness of cost control. And work motivation is able to moderate the relationship between the application of responsibility accounting to the effectiveness of cost control. Keywords: Responsibility Accounting; Cost Control; Work  Motivation.